Spiritual exercises (Journal of Parents and Teachers, 2026)
Spiritual exercises are a way of freeing the will and facilitating a personal encounter with God. It is a fundamental process that transforms the individual from an internal monologue into a dialogue with reality. It consists of four stages that help to form people capable of helping others to become fully human.
Keywords: Spirituality; Will; God